Assessment of Willingness to Pay for Wetlands Protection in Ondo State, Nigeria - Arifalo S. F (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
Wetlands provide numerous kinds of advantages and functions, making them vital ecosystems. However, the exploitation of these resources has led to their significant depletion. Engaging communities who rely on wetlands in their sustainable management is crucial to stem the degradation of these critical habitats. This research investigated the willingness of individuals to donate financially to the conservation of wetlands in Ondo State, Nigeria. It aimed to identify the factors influencing the community's willingness to pay (WTP) and to measure the financial commitment made to wetland restoration. A systematic multi-phase sample method was used to survey 124 people who lived close to wetlands. The Binary Probit Regression Model (BPRM), the Contingent Valuation Method (CVM), and descriptive statistics were all included in the analysis. The results show that the majority of respondents (64.5%) were men, with an average age of 60 and a typical household size of six people. The importance of wetlands as water reserves was emphasized by more than half of the respondents (52%) to the survey. Moreover, 53% of respondents said that they would be willing to contribute financially to the conservation of wetlands, with an average monthly payment of ₦1038.68. Gender, household size, proximity to wetlands, and yearly income were found to be significant predictors of WTP for wetland preservation in the BPRM analysis. The study highlights the community's overall willingness to contribute to wetlands protection. It promotes laws and initiatives meant to raise regional revenues and encourage more community participation in wetland preservation.